No tillage with plastic re-mulching enhances yield stability and maintains high water productivity of maize by improving water eco-physiology and root traits in northwest oasis regions - Liping Wang; Wen Yin; Pan Li; Yao Guo; Lianhao Zhao; Pingxing Wan; Diankai Zhang; Zhilong Fan; Falong Hu; Wei He; Yunyou Nan; Qiang Chai; et al. (Agricultural Water Management)
Plastic mulching is widely used in traditional maize production system, but its excessive application has led to diminishing returns in yield improvement and water productivity. No tillage with plastic re-mulching offers a sustainable alternative by reducing plastic input and regulating soil hydrothermal conditions, potentially ensuring high and stable yields along with improved water productivity. However, the underlying mechanisms linking this approach to yield sustainability and water use efficiency through water eco-physiological and root traits remains unclear. This study aims to investigate the effect of different plastic mulching strategies on water eco-physiology, root traits, grain yield, and water productivity in maize production. In 2013, a field experiment took place in the northwestern area of China, utilizing data collected between 2021 and 2023, comparing three plastic mulching treatments: (1) no tillage with plastic re-mulching (NTP), (2) no tillage in autumn and new plastic mulching in spring (RTP), and (3) conventional tillage with annual new plastic mulching (CTP, the control). Compared to CTP, NTP increased net photosynthetic rate, transpiration rate, and leaf water use efficiency by 26.1 %, 8.7 %, and 16.2 %, respectively, at 90–120 d after sowing. NTP also expanded canopy cover by 5.3 % at 75 d after sowing. Soil evaporation was reduced by 36.2 % and 24.5 % at 90–105 and 105–135 d after sowing, respectively, while soil water storage increased by 12.0 % and 7.1 %. Meanwhile, transpiration rose by 5.2 % and 17.3 %, leading to an 8.8 % increase in the transpiration-to-soil evaporation ratio. During the filling stage, NTP enhanced root development in the 0–30 cm soil layer, with increases of 35.6 % in root length density, 32.8 % in root surface area density, 32.2 % in root dry weight density, and 25.2 % in root biomass. In the 30–60 cm soil layer, root parameters also improved, with root activity and root zone water uptake rate increasing by 24.4 % and 6.5 %, respectively. Consequently, NTP increased grain yield by 5.5 %, with higher yield stability driven by a 6.8 % increase in harvested ears and a 9.1 % rise in1000-kernel weight, while maintaining water productivity comparable to CTP. These findings provide theoretical support for reducing plastic use while maintaining maize yield stability and water productivity in arid irrigated regions.